Associations of maternal hyperglycemia in the second and third trimesters of pregnancy with prematurity - Zhao, Dong (Medicine (Baltimore), 2020)
Hyperglycemia in pregnancy (HIP) is related to adverse pregnancy outcomes. However, women with hyperglycemia in the second and third trimester of pregnancy (HISTTP) were not been observed. We aim to reveal associations between HISTTP and prematurity. To confirm which risk factor is better in predicting preterm delivery. This retrospective study included 660 patients, of which 132 have HISTTP and 528 have euglycemia. Univariate analysis was used to extract risk factors and multivariates logistic regression analysis to obtain odds ratio (OR) for prematurity. Mean decrease gini (MDG) in random forest algorithm was used to rank the risk factors. HISTTP women have higher prepregnancy BMI and a higher percentage of family history of hypertension, maternal adiposity, maternal anemia, gestational diabetes mellitus (GDM), prematurity, neonatal asphyxia in 1-minute (P < .05). Univariate analysis of prematurity showed that preterm women had higher rate of HISTTP (P < .01), second births, elderly pregnancy, hypertention, family history of hypertention and multiple perinatal infant (P < .05). Multivariate logistic regression analysis indicates that HISTTP (OR = 2.984, P = .0017), maternal hypertension (OR = 5.208, P = .001) and multiple perinatal infants (OR = 59.815, P < .0001) are independent risk factors for prematurity. After ranked the MDG, the top 3 risk factors were multiple perinatal infants, maternal hypertension, HISTTP. MDG of HISTTP is higher than that of GDM. Women with HISTTP deserve to be concerned, whose prematurity rate are increased. HISTTP is an independent risk factor and a better predictor of prematurity.